Potential protective role of interferon-induced protein with tetratricopeptide repeats 3 (IFIT3) in COVID-19 - de Castro, Mateus V.; Cariste, Leonardo M.; Almeida, Rafael R.; Sasahara, Greyce L.; Silva, Monize V. R.; Soares, Flávia B.; Coria, Vivian R.; Naslavsky, Michel S.; Santos, Keity S.; Cunha-Neto, Edecio; Kalil, Jorge; Zatz, Mayana (Frontiers in Cellular and Infection Microbiology, 2024)
The COVID-19 pandemic has prompted a quest to understand why certain individuals remain uninfected or asymptomatic despite repetitive exposure to SARS-CoV-2. Here, we focused on six exposed females residing with their symptomatic and reinfected SARS-CoV-2 PCR-positive COVID-19 partners. Peripheral blood mononuclear cell samples from couples were analysed for poly (I:C)-induced mRNA expression of type I/III interferons and interferon-stimulated genes (ISGs). Remarkably, we found a significant upregulation of the ISG interferon-inducible protein with tetrapeptide repeats 3 (IFIT3) gene exclusively in exposed uninfected or asymptomatic females, suggesting a potential role in protective immunity against symptomatic COVID-19.